Pengembangan Sistem Monitoring Pemeriksaan Pasien di Instalasi Kedokteran Nuklir Berbasis Open-Source ERP dengan Metode Quickstart - Diandra Muhammad Lutfi; Umar Yunan Kurnia Septo Hediyanto; Ari Yanuar Ridwan; Kharisma Perdani Kusumahstuti (Journal of Information System Research (JOSH), 2023)
As a national reference center for nuclear medicine services, the general hospital in the Bandung area is required to consistently enhance the quality of its services, including improving patient care and reducing errors that occur during the patient examination process. Currently, the nuclear medicine installation department offers 45 types of examination services, resulting in a high volume of daily patient examinations. This situation presents a distinct challenge for the nuclear medicine installation department as it lacks a system for monitoring patient examinations. The issue of data and information integration becomes crucial in patient examination activities, particularly because a lack of integration can lead to suboptimal examination reporting processes. This research aims to develop an monitoring system for patient examination activities using the Odoo application, employing the Quickstart development method. The primary focus of this study is on the integration of data and information in monitoring patient examinations. Each patient examination data can be input into the Odoo application, centralizing the storage of data and information. This research aims to offer a solution to the challenges faced by integrating business processes with patient examination monitoring systems. It also proposes data and information integration within patient examination activities and other departments within the nuclear medicine installation. This integration will result in a well-structured reporting system that is easy to generate, providing various forms of patient examination reports as an outcome.